PERILAKU APARATUR DALAM PENDISTRIBUSIAN BERAS MISKIN DI KELURAHAN BENUA MELAYU DARAT KECAMATAN PONTIANAK SELATAN - E.21108053, Murtiati (FISIP Universitas Tanjungpura, 2013)
In principle, the government in carrying out the public service has three main functions, and one of these functions is to provide protection which will then bring forth the goods and services needed by the community or the public. Giving rice for the poor (Raskin) into a form of social protection of the government that aims to ensure access of the poor to food sufficiency. The focus in this study refers to the principles of the distribution of Raskin take sides of apparatus to Target Households Beneficiaries (RTS-PM) Raskin, transparency, participation, and accountability apparatus in service Raskin. To discuss the focus of the study, used qualitative methods and case study research conducted in Kelurahan Benua Melayu Darat Kecamatan Pontianak Selatan. Based on the results of the study found that the Raskin distribution in Kelurahan Benua Melayu Darat seems less than optimal, and one contributing factor is the distribution of Raskin is not in accordance with the provisions set forth by the local government. Therefore, the researchers suggested that the data is updated every year Raskin recipients by involving the village (RT and RW) that does not happen again in the distribution of Raskin wrong target, it is expected that the implementation team Raskin village level to always announce to the public openly about the distribution of Raskin in its territory, preferably related agencies (Government of Pontianak) make rules about complaints and the management of public complaints about the problems of villages raskin distribution service. In addition, the need for socialization and training for personnel in charge of serving the distribution of Raskin.Keywords:Â Government take sides to public, Transparency Distribution of Raskin, Participation of Society, Government Accountability.